Integrating Business Models into Public Policy for Sustainable Transport in Batam City - Enos Paselle; Etika Khairina; Agus Priyanto; Fathul Qarib (Journal Public Policy, 2026)
This study aims to show how the government innovates in realizing sustainable development in transportation, and how the transition path of developing regions in this study focuses on the Batam city, accelerating change through public policy with a business approach. This study uses a qualitative descriptive approach, with primary and secondary data sources. Primary through observation, observation interviews, documentation, and focus group discussions. Meanwhile, secondary sources come from research results, literature studies, and documentation from the Batam city government and the mass media. The analysis technique uses triangulation assisted by the NVivo 14 tools application. The results of the study show that there are three programs that the government can utilize through a business approach to accelerate sustainable transportation, namely energy transition, mobility services, and multimodal infrastructure development. The energy transition can be carried out by implementing electric transportation even in long-term development. This step hurts the sustainability of electrical energy sources, but its externalities minimize the dissolution of fuel use. one of which is possible is park and ride which can connect the community with digital-based public services, and finally Batam City as an industrial city can utilize the private sector/companies as third parties (multilevel perspective), The interaction between the two will be on each other which can continue through integration to achieve alignment of goals according to the concept of sustainable development targets.